A review of the ant genus Myrmecorhynchus (Hymenoptera: Formicidae) - Shattuck, S.o. (Zootaxa, 2015)
The Australian endemic ant genus Myrmecorhynchus is reviewed. The genus is known from three species (M. carteri Clark, M. emeryi André and M. nitidus Clark) which are restricted to eastern and southern Australia. Myrmecorhynchus musgravei Clark and M. rufithorax Clark are newly synonymised with M. emeryi André. All species are found in forested areas where they nest arboreally or, less commonly, in soil. Foraging occurs primarily on vegetation and tree trunks.